Zasób, kapitał czy człowiek? Współczesne trendy w zarządzaniu pracownikami - Marek, Agnieszka (Annales. Etyka w Życiu Gospodarczym, 2014)
People should be at the centre of attention within knowledge-based economics. The leaders of each enterprise ought to focus on providing the best conditions for their employees’ professional and individual development and treat them with respect in terms of their dignity and needs. In contemporary literature two notions in perceiving people in organisations are noticeable. The first one treats employees as ‘resources’ which have to be properly used or as ‘capital’ that should bring a decent return on investment. The second notion derives a lot from Christian philosophy and sees the human as a person who treats work as a way to realize his calling and thus is able to take responsibility for the decisions made and actions taken. Acting in a constantly changing environment, people have to be flexible and able to take advantage of emerging opportunities and avoid threats. Within this process it is not a matter of being a human ‘being’ but rather becoming, which means that they are incessantly developing their potential. Although it is hard to predict human behaviour, the main task for managers is to lead in a way that will help employees use their full potential for both their own and the company’s benefit.